Pengaruh Dukungan Sosial dan Pengalaman Hidup Terhadap Psychological Well-Being Pada Remaja Tunarungu Berprestasi - Firmanda, Yori (Journal of Educational Research and Humaniora (JERH), 2024)
The aim of this study is to investigate the impact of social support and life experience on psychological well-being of achieving deaf adolescents in West Sumatra. This research utilizes quantitative research methods. The sampling technique employed in this study is nonprobability sampling. The study included 270 achieving deaf adolescents. Data was collected using a Likert scale questionnaire with five alternative answers. Data analysis was conducted using multiple linear regression analysis with AMOS software version 26. The results of the study indicate that social support has a direct and significant influence on psychological well-being of achieving deaf adolescents in West Sumatra. Additionally, life experience has an immediate and significant impact on psychological well-being of achieving deaf adolescents in West Sumatra. Parametric tests of multiple linear regression analysis revealed C.R = 8.418 for social support on psychological well-being, C.R = 5.869 for life experience on psychological well-being, and a significant p-value of 0.000 for both variables., for p=0,000 is a significant value for both variables.